2010
DOI: 10.1123/jab.26.4.484
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic and Kinetic Analysis of the Fouetté Turn in Classical Ballet

Abstract: The fouetté turn in classical ballet dancing is a continuous turn with the whipping of the gesture leg and the arms and the bending and stretching of the supporting leg. The knowledge of the movement intensities of both legs for the turn would be favorable for the conditioning of the dancer’s body. The purpose of this study was to estimate the intensities. The hypothesis of this study was that the intensities were higher in the supporting leg than in the gesture leg. The joint torques of both legs were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…13 Previous biomechanical measures of dance performance have centered on the use of kinetic (ground reaction forces) [14][15][16] and kinematic (three-dimensional motion capture systems) analysis. [17][18][19] However, these methods are often labor intensive, generally observe one participant at a time, and cannot provide real-time live feedback. 20 These drawbacks, coupled with extensive data download and analysis, call into question the ability of such technologies to influence day-to-day dance practice.…”
mentioning
confidence: 99%
“…13 Previous biomechanical measures of dance performance have centered on the use of kinetic (ground reaction forces) [14][15][16] and kinematic (three-dimensional motion capture systems) analysis. [17][18][19] However, these methods are often labor intensive, generally observe one participant at a time, and cannot provide real-time live feedback. 20 These drawbacks, coupled with extensive data download and analysis, call into question the ability of such technologies to influence day-to-day dance practice.…”
mentioning
confidence: 99%
“…Although there is little information on the kinematic patterns of replaced hip joints during dance activities, these kinematic data should be beneficial for advising patients according to the type of physical activity. Motion capture systems with reflective markers have been widely used for in vivo joint kinematics even during classical ballet [2224]. Quanbeck et al [22] reported that bilateral hip external rotation during turnout in classical ballet was 49°.…”
Section: Discussionmentioning
confidence: 99%
“…Previous efforts have focused on understanding how dancers produce angular impulse around the vertical axis during rotational movements such as fouetté, pirouette, and piqué turns. [6][7][8][9] Dancers interact with the ground to initiate and stop angular impulse through modulating ground reaction forces and free moments in the transverse plane. 6,10 As Holden and Cavanagh 11 explained, the free moment is a force couple about the vertical axis that passes through the center of pressure, representing a frictional moment between the individual and ground.…”
mentioning
confidence: 99%
“…6,10 As Holden and Cavanagh 11 explained, the free moment is a force couple about the vertical axis that passes through the center of pressure, representing a frictional moment between the individual and ground. From a bottom-up inverse dynamics perspective, free moments can be transferred proximally and result in loads on segments and joints such as the tibia and knee, 8 and rotational loads can strain ligaments around the knee joint. 12 Although the free moment has been studied as a factor associated with dance performance, 6 more research is warranted.…”
mentioning
confidence: 99%